The real in the magic: a study of magic realism in Salman Rushdie’s Haroun and the sea of stories (1990) - Ali, Nuurzahirah; Mohd Ramli, Aimillia (Penerbit Universiti Sains Malaysia, 2019)
While many studies have focused on Salman Rushdie’s use of magic realism in his highly-acclaimed novels, the way it is employed in his children’s fiction remains understudied. This paper, hence, attempts to fill in this gap by applying Anne Hegerfeldt’s (2005)’s theoretical framework on magic realism onto its reading of Salman Rushdie’s Haroun and the Sea of Stories (1990). This framework relies on five techniques or features namely: a realist mode of writing to describe fantastic events and characters; a marginalized focaliser; subverted scientific and historical discourses; a supernatural reality; and, finally, a literal manifestation of a figurative expression. This paper also suggests that Rushdie employs magic realism to undermine the realist narrative mode as well as scientific and historical discourses in order to present an alternative worldview that places narrative knowledge, gathered from stories with magical characters and events, as a legitimate source of knowledge regarding the world.